Maternal 'near miss' collection at an Australian tertiary maternity hospital - Skandarupan Jayaratnam; Sonia Kua; Caroline deCosta; Richard Franklin (BMC, 2018)
Abstract Background Australia has a maternal mortality ratio of 6.8/100000 live births, a rate akin to other developed countries and consistent with the high level care provided within the Australian health care system. With maternal mortality at very low levels assessment of severe maternal morbidity is increasingly being used as an indicator of quality of care and to identify areas for improvement in maternity services. The WHO maternal 'near miss' criteria is a standardised tool has been increasingly used worldwide to assess maternal morbidity and standards of maternity care. The aim of this study was to determine the rate and aetiology of maternal 'near misses' at King Edward Memorial Hospital (KEMH) using the WHO near miss criteria. Methods Cases of maternal 'near miss' were prospectively identified at KEMH using the WHO near miss criteria over a period of 6 months (1st December 2014 to 31st May 2015). A descriptive analysis of the results was undertaken. Results During the study there were 2773 live births with 19 women who had 'near miss' presentations. There were no maternal deaths. The maternal 'near miss' index rate was 7/1000 live births. The main causes of obstetric 'near miss' were obstetric haemorrhage, pre-eclampsia and early pregnancy complications. Conclusion The rate of maternal 'near miss' at KEMH was 7/1000 live births and post-partum haemorrhage was identified as the most common aetiology, consistent with other studies in developed countries. Further research comparing currently utilised local, state and national morbidity systems would allow further validation of the WHO near miss criteria in Australian settings. The study presented in this publication was undertaken at King Edward Memorial Hospital, 374 Bagot Rd., Subiaco WA 6008.